In situ fabrication of highly porous foam-like Zn nanostructures on gas diffusion layer for selective electrocatalytic reduction of carbon dioxide to carbon monoxide - Jeong Juwon; Choi Jiwoo; Jang Segeun; Shin Heejong; Kim Sungjun; Jang Junghwan; Park Hyun S.; Choi Mansoo; Sung Yung-Eun (한국공업화학회, 2022)
Electrochemical reduction of CO2 is regarded as a promising technique for converting unwanted CO2 into high-value chemicals. Among the various electrocatalysts that are crucial for overcoming sluggish reduction processes, Zn has been continuously studied because of its suitable catalytic activity and abundance in the earth's crust. In this study, we fabricated highly porous foam-like Zn nanostructures on a gas diffusion layer (GDL) using hydrothermal growth and in situ reduction process. The prepared electrode showed a CO partial current density of 20.9 mA.cm(-2) at -1.10 V, which is approximately 10 times higher than that of the bare Zn foil. Moreover, the fabricated electrode can be directly applied to the large-scale flow cell system without further modification. The flow cell system with the fabricated electrode showed a current density of approximately 200 mA.cm(-2) and CO faradaic efficiency of 75% on a 2 h long experiment at 2.7 V cell voltage, which clearly confirms the possibility of highly porous Zn nanostructures on GDL. (C) 2022 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.